Subsequent Acute Ischemic Stroke in a Patient with Monocular Vision Loss Associated with Isolated Internal Carotid Artery Occlusion: A Case Report - Jessica Seetge; Balázs Cséke; Zsófia Nozomi Karádi; Eszter Szalai; Valéria Gaál; László Szapáry (Neurology International)
Background/Objectives: Acute retinal ischemia, including central retinal artery occlusion (CRAO), is recognized as a stroke equivalent by the American Heart Association/American Stroke Association (AHA/ASA), necessitating immediate multidisciplinary evaluation and management. However, referral patterns among ophthalmologists remain inconsistent, and evidence-based therapeutic interventions to improve visual outcomes are currently lacking. CRAO is associated with a significantly elevated risk of subsequent acute ischemic stroke (AIS), particularly within the first week following diagnosis, yet the role of intravenous thrombolysis (IVT) in this setting remains controversial. This case report presents a unique case of CRAO with concurrent internal carotid artery (ICA) occlusion, followed by an AIS affecting the middle cerebral artery (MCA). Case presentation: An 83-year-old woman presented with acute, painless monocular vision loss to the emergency department. IVT was administered within 4.5 h of admission for suspected CRAO associated with ICA occlusion (ICAO) identified on CT-angiography (CTA). One hour post-thrombolysis, CT-perfusion (CTP) confirmed MCA occlusion (MCAO), necessitating mechanical thrombectomy (MT). Successful recanalization was achieved without complications, and the patient demonstrated no functional impairments at discharge. Conclusions: This case underscores the importance of maintaining a vigilant approach to stroke management in CRAO patients. It highlights the diagnostic challenges encountered in clinical practice and advocates for further research into the role of IVT in CRAO cases with ICAO, emphasizing the need for consensus in treatment.